2014
DOI: 10.1002/2013ja019684
|View full text |Cite
|
Sign up to set email alerts
|

The location of magnetic reconnection at Saturn's magnetopause: A comparison with Earth

Abstract: Data from the Cassini Electron Spectrometer are used to investigate the location of magnetic reconnection at Saturn's magnetopause. Heated, streaming electron distributions in the boundary layer on the magnetosheath side of the magnetopause are evidence of reconnection and an open magnetopause. A model for the location of reconnection is used to compare the modeled and observed streaming direction of the heated electron distributions. Magnetic reconnection at Saturn's magnetopause is predicted and observed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(105 citation statements)
references
References 54 publications
6
98
0
1
Order By: Relevance
“…It is thus expected that reconnection at Saturn's magnetopause is generally limited to regions of the magnetopause surface where the fields on either side of the boundary become almost antiparallel (note that this is presently consistent with observed reconnection signatures, e.g. Fuselier et al 2014). More recently, reported the results of a study that was similarly based on measured near-magnetopause conditions.…”
Section: Magnetic Reconnectionsupporting
confidence: 62%
See 1 more Smart Citation
“…It is thus expected that reconnection at Saturn's magnetopause is generally limited to regions of the magnetopause surface where the fields on either side of the boundary become almost antiparallel (note that this is presently consistent with observed reconnection signatures, e.g. Fuselier et al 2014). More recently, reported the results of a study that was similarly based on measured near-magnetopause conditions.…”
Section: Magnetic Reconnectionsupporting
confidence: 62%
“…In the case of Saturn's magnetosphere, in situ evidence for magnetopause reconnection has also been reported (Huddleston et al 1997;McAndrews et al 2008;Lai et al 2012;Fuselier et al 2014), and it has been suggested that some dayside auroral features are caused by bursts of magnetopause reconnection (Radioti et al 2011a;Badman et al 2012a. However, unlike Jupiter, no examples of FTEs have been identified to date (Lai et al 2012), and neither Saturn's auroral power nor the thickness on the magnetospheric boundary layer adjacent to the magnetopause show a clear response to the orientation of the IMF (unlike the case of Earth's magnetopause reconnection-driven magnetosphere) Clarke et al 2009;.…”
Section: Magnetic Reconnectionmentioning
confidence: 89%
“…Hence, dayside magnetopause reconnection is thought to be less common at Saturn than at Earth. Models of Saturn's magnetopause reconnection reveal also that reconnection is more likely to occur at higher latitudes [Desroche et al, 2013;Fuselier et al, 2014]. For instance, unlike at Earth, the IMF orientation does not strongly influence the thickness of Saturn's low-latitude boundary layer [Masters et al, 2011] nor the magnetopause location [Lai et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…To combat this difficulty, this study uses results from the maximum magnetic shear model [ Trattner et al ., , ] for Cluster 3 crossings from 2001 to 2009 to identify crossings possibly near reconnection sites at the magnetopause. This model has been used previously for Earth and Saturn to identify the most probable location of reconnection across the magnetopause [e.g., Fuselier et al ., ; ; Trattner et al ., ; Vines et al ., ].…”
Section: Introductionmentioning
confidence: 99%